Insights from 180 years of mitochondrial variability in the endangered Mediterranean monk seal (Monachus monachus). Issue 4 (24th April 2019) - Gaubert, Philippe; Justy, Fabienne; Mo, Giulia; Aguilar, Alex; Danyer, Erdem; Borrell, Asunción; Dendrinos, Panagiotis; Öztürk, Bayram; Improta, Roberta; Tonay, Arda M.; Karamanlidis, Alexandros A.
Abstract: Mediterranean monk seals (MMS) are among the most endangered marine mammals on Earth. We screened mitochondrial variability (control region [CR1] and mitogenomes) of the species through a 180‐yr timeframe and extended by 20% ( n = 205) the number of samples from a previous investigation, including historical specimens from 1833 to 1975. Although we detected two new, rare CR1 haplotypes, genetic diversity remained extremely low. Fully resolved haplotype median network and rarefaction analysis both suggested low probability for further unscreened haplotypes. There was no clear phylogeographic structure across the 12 marine subdivisions covered by the species' range. Haplotypes previously considered diagnostic of the extant North Atlantic and eastern Mediterranean populations had their distributions extended into the western Mediterranean and the North Atlantic, respectively, by both historical and recent samples. Our study suggests that MMS have been genetically depauperate since at least the mid‐19th century, and that the massive 1997 die‐off in Western Sahara (North Atlantic) could have caused local haplotype extinctions. Our results support the hypothesis of past metapopulation dynamics across the species range, where the current segregation into geographically distant and genetically depauperate breeding populations ( i.e ., North Atlantic and eastern Mediterranean Sea) derives from the combined effects of historical extinctions, genetic drift on small breeding groups, and persistently low levels of genetic diversity.